Terceirização em uma empresa de manufatura com classe A em excelência operacional. - Tognetti, Mauro Athos (Universidade Federal de São Carlos, 2004)
This work has the objective to analyze and to discuss the organizational transformations in the supply chain of a worldwide competitive manufacturing company operating with MRP II Class A, JIT and TQM management systems, caused by the strategic outsourcing implementation for tree thousands, two hundreds and third eight components involving ten key suppliers. The work analyzes the SCM concepts required to the global competitiveness, the buyer / supplier partnership relationships, the transformations in the purchasing organizations within the MRP II, JIT and TQM environment and some work frames for strategic outsourcing. It analyzes the main phases of one strategic outsourcing case study: the outsourcing decision criteria based on the definition of the core competences of the leader company, the group technology concepts used to link the outsourced items with the supplier s core competences, the supplier selection process, the partnership contracts, the quotation and negotiation process performed by common group of items; the project management process used to control the high amount of outsourcing activities and the supplier s learning curves control. Four years had already gone since this strategic outsourcing process was implemented and all the suppliers involved had their performances complied with the annual targets established by the Supplier Chain leader company. So, the conclusion is that the process implementation of this strategic outsourcing was correct.
Keywords: Gestão de suprimentos; Gestão da cadeia de suprimentos; Planejamento estratégico; Compras; Parceria; Supply chain management; Strategy planning; Purchasing; Partnership; Strategic outsourcing; Supplier development; ENGENHARIAS::ENGENHARIA DE PRODUCAO